1996
DOI: 10.1111/j.1439-0434.1996.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Moniliformin Accumulation and other Effects of Fusarium avenaceum (Fr.) Sacc. on Kernels of Winter Wheat Cultivars

Abstract: Accumulation of the mycotoxin moniliformin (MON) and other effects on kernels were examined in 13 Polish winter wheat cultivars inoculated with E. avenaceum (Fr.) Sacc. isolate ATCC 64451. Kernels from inoculated ears were divided into three fractions: Eusarium damaged kernels (FDK), kernels with black point symptoms (BPK) and healthy looking kernels (HLK). The average moniliformin content (mg/kg) was highest in chaff (11.69), lower in infested kernels (FDK -)-BPK) (2.70) and lowest in HLK (1.16). The mean lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
3
12
1
2
Order By: Relevance
“…Nevertheless, both species are common in Central and Northern Europe. The frequency of Fusarium species on cereals in Poland varies because of the significant variation in weather conditions [5,13,15,28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, both species are common in Central and Northern Europe. The frequency of Fusarium species on cereals in Poland varies because of the significant variation in weather conditions [5,13,15,28].…”
Section: Resultsmentioning
confidence: 99%
“…However, Goliński et al [28] found F. poae (64%), F. tricinctum (15%), F. avenaceum (8%), F. culmorum (6%) and F. graminearum (4%) as the most common species infecting wheat heads in Poland. High incidence of F. avenaceum in Dębina ( Table 2) was related probably to the geographical locationcooler weather conditions are usually favorable for this species [10].…”
Section: Resultsmentioning
confidence: 99%
“…Fusarium avenaceum has been reported as one of the most frequently isolated Fusarium species from cereals in Norway Langseth et al, 1997), Finland (Yla-Mattila et al, 2002, Poland (Golinski et al, 1996), England (Parry et al, 1995) and Germany (Schu¨tze et al, 1997). Because information on the infection process of F. avenaceum in wheat spikes is limited, penetration and colonization of wheat spikes by F. avenaceum was examined in this study by SEM and TEM.…”
Section: Introductionmentioning
confidence: 98%
“…Epidemics of FHB result in a significant yield reduction and low quality of grains (Boyacioglu and Hettiarachchy, 1995), but also in contamination of grains with mycotoxins produced by the pathogens (Snijders and Perkowski, 1990;Golinski et al, 1996). The mycotoxins have been shown to be harmful to human and animal health (Desjardins and Hohn, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesis of toxic secondary metabolites (including trichothecene myocotoxins) and their accumulation in kernels and various tissues of cereals [24] is one of the factors differing aggressiveness of pathogenic strains [5]. Moniliformin is produced by F. avenaceum and is accumulated in significant amounts in wheat kernels, often in co-occurrence of other toxic metabolites rendering situation more hazardous in animal and human health [7]. In Poland, natural contamination of cereals by Fusarium mycotoxins was reported [4,6,8,21,25].…”
Section: Introductionmentioning
confidence: 99%